Brassinosteroids enhance BES1‐required thermomemory in Arabidopsis thaliana. (3rd October 2022) - Yao, Xiuhong; Li, Yanling; Chen, Juan; Zhou, Zuxu; Wen, Yu; Fang, Ke; Yang, Fabin; Li, Taotao; Zhang, Dawei; Lin, Honghui
Abstract: Heat stress (HS) caused by ambient high temperature poses a threat to plants. In the natural and agricultural environment, plants often encounter repeated and changeable HS. Moderate HS primes plants to establish a molecular 'thermomemory' that enables plants to withstand a later‐and possibly more extreme‐HS attack. Recent years, brassinosteroids (BRs) have been implicated in HS response, whereas the information is lacking on whether BRs signal transduction modulates thermomemory. Here, we uncover the positive role of BRs signalling in thermomemory of Arabidopsis thaliana . Heat priming induces de novo synthesis and nuclear accumulation of BRI1‐Ethyl methyl sulfon‐SUPPRESSOR (BES1), which is the key regulator of BRs signalling. BRs promote the accumulation of dephosphorylated BES1 during memory phase, and stoppage of BRs synthesis impairs dephosphorylation. During HS memory, BES1 is required to maintain sustained induction of HS memory genes and directly targets APX2 and HSFA3 for activation. In summary, our results reveal a BES1‐required, BRs‐enhanced transcriptional control module of thermomemory in Arabidopsis thaliana .